Pengaruh Penilaian Prestasi Kerja dan Kompensasi Terhadap Motivasi Kerja Serta Dampaknya Terhadap Kinerja Karyawan pada PT. Bank Central Asia Tbk Kantor Cabang Utama Jambi - Dewi Marlinda; Fakhrul Rozi Yamali; M Zahari MS; Fakhrul Rozi Yamali (Universitas Batanghari, 2021)
The purpose of this research is to obtain an overview of the assessment of work performance, compensation, work motivation and employee performance at PT. BCA Tbk KCU Jambi; and to know the effect of work performance assessment and compensation directly and indirectly on employee motivation and performance; and to know the influence of motivation on performance. The population in this study was employees at PT. Bca. Tbk KCU Jambi with a total of 125 employees. The size or number of samples in this study was determined based on the theory developed by Slovin with a value of e = 10%, so that 56 samples were obtained. Analysis techniques use path analysis to see direct and indirect influence, and continued by testing R Square and hypothesis testing partially and simultaneously with t test and F test. Where based on the results of t test (partial) and test F (Simultaneous) shows that the assessment of work performance and compensation has a significant and positive influence on motivation and performance, as well as motivation also has a significant and positive influence on performance. This explains that if the assessment of work performance and compensation can be carried out properly, it will have a positive influence in improving the motivation of work that has implications for improving employee performance at PT. BCA Tbk KCU Jambi. Based on some of the conclusions obtained, the suggestions that can be given in this study include the future expected leadership of PT. Bank Central Asia. Tbk Jambi Main Branch Office can carry out performance assessments carried out objectively. In addition, this research needs to be followed up again to see what factors can affect employee performance comprehensively, in order to answer other factors (epsilon) that affect employee performance.